2012
DOI: 10.1100/2012/427941
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation in Tinnitus Patients: A Systemic Review and Meta-Analysis

Abstract: Although transcranial direct current stimulation (tDCS) has already been used to manage tinnitus patients, paucity of reports and variations in protocols preclude a comprehensive understanding. Hence, we conducted a meta-analysis based on systemic review to assess effectiveness of tDCS in tinnitus management and to compare stimulation parameters. PubMed was searched for tDCS studies in tinnitus. For randomized controlled trials (RCTs), a meta-analysis was performed. A total of 17 studies were identified and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 56 publications
2
73
0
Order By: Relevance
“…Research on tDCS has burgeoned during the last 2 decades, and experimental indications for it include depression, [22][23][24] tinnitus, 25 motor paresis in patients with chronic stroke, 26 poststroke aphasia, 27 chronic pain, 28 and other conditions. This procedure has also been used as an investigative tool to study brain functioning.…”
Section: What Is Tdcs and Why May It Be Useful For Refractory Auditormentioning
confidence: 99%
“…Research on tDCS has burgeoned during the last 2 decades, and experimental indications for it include depression, [22][23][24] tinnitus, 25 motor paresis in patients with chronic stroke, 26 poststroke aphasia, 27 chronic pain, 28 and other conditions. This procedure has also been used as an investigative tool to study brain functioning.…”
Section: What Is Tdcs and Why May It Be Useful For Refractory Auditormentioning
confidence: 99%
“…TDCS involves two electrodes sending a low current through the brain. Some studies have shown tinnitus relief after tDCS for 82% [26] of the cohort studied while others have only shown improvement for 39.5% [27]. A study by Rabau et al examined the effect of tDCS in combination with TRT.…”
Section: Treatment Strategies For Tinnitusmentioning
confidence: 99%
“…However, as a result of empirical and clinical observation trials, it was indicated that the present applications provide only a partial response to the treatment (10). A significant reason of the low success rate of treatment response is that the methods used target developing methods to cope with tinnitus rather than reducing the perception of it (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, as a result of empirical and clinical observation trials, it was indicated that the present applications provide only a partial response to the treatment (10). A significant reason of the low success rate of treatment response is that the methods used target developing methods to cope with tinnitus rather than reducing the perception of it (10). On the other hand, the lack of a diagnostic method to differentiate objectively the various subforms of tinnitus is considered to be among the greatest obstacles before treatment of tinnitus (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation